Hepatitis B virus infection seromarkers among college freshmen and their immune responses to different vaccination policies of hepatitis B vaccine - Yuyang Xu; Yan Liu; Jun Wang; Xinren Che; Xuechao Zhang; Wei Jiang; Jian Du; Xiaoping Zhang; Wenwen Gu (Taylor & Francis Group, 2021)
Background College students are one of the susceptible population of Hepatitis B virus (HBV) infection. We aim to delineate HBV infection seromarkers among college freshmen and to evaluate immunological response of vaccination immunization for hepatitis B vaccine (HepB). Methods A simple random sampling method was adopted to select subjects and who met the "inclusion and exclusion criteria" and who with history of vaccination were selected as the observation objects. HBsAg and anti-HBs levels were detected before revaccination. Subjects with negative anti-HBs before immunization were inoculated with 20 ug HepB according to the 0-1-6 procedure and those with weak positive anti-HBs before immunization were inoculated with 1-dose 20 ug HepB. Anti-HBs levels were detected after HepB booster. Combined with the results of anti-HBs, their immune response to HepB and influencing factors in freshmen were investigated. Anti-HBs before immunization was negative and ≥10 m IU/ml after immunization was considered positive conversion; anti-HBs before immunization was weak positive and anti-HBs≥100 m IU/ml after immunization was also considered positive conversion. Results A total of 10645 freshmen were included. The total rate of HBsAg carriers was 0.6% (63/10645), and the strong positive rate of anti-HBs was 16.1% (1706/10645), the weak positive rate was 14.4% (1526/10645).1286 freshmen were vaccinated with HepB and completed the questionnaire survey. About 79.0% (154/195) of freshmen's anti-HBs turned strong positive after receiving 1-dose HepB and 100.0% (1091/1091) turned positive after receiving 3-doses HepB. The Geometrical Mean Titer (GMT) of anti-HBs was significantly influenced by gender, registration and the immunization doses of HepB. Conclusion The HBsAg carrying rate and anti-HBs positive rate of college freshmen were low, and the HepB has a good effect on the immunity of college freshmen. Increasing the immunization rate of HepB is very important for the prevention and control of hepatitis B.